Potent neutralization by monoclonal human IgM against SARS‐CoV‐2 is impaired by class switch. (12th May 2022) - Callegari, Ilaria; Schneider, Mika; Berloffa, Giuliano; Mühlethaler, Tobias; Holdermann, Sebastian; Galli, Edoardo; Roloff, Tim; Boss, Renate; Infanti, Laura; Khanna, Nina; Egli, Adrian; Buser, Andreas; et al.
Abstract: To investigate the class‐dependent properties of anti‐viral IgM antibodies, we use membrane antigen capture activated cell sorting to isolate spike‐protein‐specific B cells from donors recently infected with SARS‐CoV‐2, allowing production of recombinant antibodies. We isolate 20, spike‐protein‐specific antibodies of classes IgM, IgG, and IgA, none of which shows any antigen‐independent binding to human cells. Two antibodies of class IgM mediate virus neutralization at picomolar concentrations, but this potency is lost following artificial switch to IgG. Although, as expected, the IgG versions of the antibodies appear to have lower avidity than their IgM parents, this is not sufficient to explain the loss of potency. Synopsis: Virus‐specific B cells of all classes can be isolated from human donors by membrane antigen capture activated cell sorting (MACACS). IgM antibodies include potent neutralizers, but potency is impaired by artificial class switch to IgG. MACACS is a powerful technique for isolating B cells specific for membrane antigens. Serum IgM from recently infected donors is self‐reactive, but monoclonal IgM from MACACS B cells are antigen specific. Isolated IgM include potent virus‐neutralizing antibodies, but this potency is dependent on the IgM structure. Abstract : Virus‐specific B cells of all classes can be isolated from human donors by membrane antigen capture activated cell sorting (MACACS). IgM antibodies include potent neutralizers, but potency is impaired by artificial class switch to IgG.